Management of Nasoalveolar Cyst by Transnasal Endoscopic Marsupialization - Mohnish Grover; Siddharth Nirwan; Rahul Nahar; Samanvaya Soni (Bengal Journal of Otolaryngology and Head Neck Surgery)
Introduction: A nasoalveolar cyst is a benign nonodontogenic mass situated in the anterior region of the maxilla. They are often located submucosally in the anterior nasal floor giving rise to swelling in the nasolabial area at the base of nasal alae. Traditionally, the approach of choice was intraoral sublabial marsupialization, however the trend is shifting to lesser invasive and scarless transnasal endoscopic marsupialization.